ChemInform Abstract: A Concise Formal Total Synthesis of Lactimidomycin. Issue 39 (September 2015) - Li, Wei; Georg, Gunda I.
Abstract The total synthesis of macrolactone ((‐)‐I), a precursor of title compound (II), from (E)‐2‐methyl‐2‐pentenoic acid is described.